2013
DOI: 10.1002/jbm.a.35041
|View full text |Cite
|
Sign up to set email alerts
|

β‐Dicalcium silicate‐based cement: Synthesis, characterization and in vitro bioactivity and biocompatibility studies

Abstract: β-dicalcium silicate (β-Ca₂ SiO₄, β-C₂ S) is one of the main constituents in Portland cement clinker and many refractory materials, itself is a hydraulic cement that reacts with water or aqueous solution at room/body temperature to form a hydrated phase (C-S-H), which provides mechanical strength to the end product. In the present investigation, β-C₂ S was synthesized by sol-gel process and it was used as powder to cement preparation, named CSiC. In vitro bioactivity and biocompatibility studies were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
(160 reference statements)
2
16
0
Order By: Relevance
“…Dicalcium silicate (Ca 2 SiO 4 ) is an important material in the calcium-silica system, which is frequently identified as an important constituent in Portland cement [ 2 , 3 ]. Previous studies have indicated that γ -Ca 2 SiO 4 ceramic possesses good bioactivity, biocompatibility, and mechanical properties and that it might be a promising bone implant material [ 4 , 5 ]. Additionally, γ -Ca 2 SiO 4 ceramic might be suitable for a potential application in the biomedical field, preferentially as materials for bone repair [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dicalcium silicate (Ca 2 SiO 4 ) is an important material in the calcium-silica system, which is frequently identified as an important constituent in Portland cement [ 2 , 3 ]. Previous studies have indicated that γ -Ca 2 SiO 4 ceramic possesses good bioactivity, biocompatibility, and mechanical properties and that it might be a promising bone implant material [ 4 , 5 ]. Additionally, γ -Ca 2 SiO 4 ceramic might be suitable for a potential application in the biomedical field, preferentially as materials for bone repair [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that silicon is an important trace element for bone regeneration and repair, which can up-regulate the expression of osteogenesis-related genes, activate the osteogenesis related signaling pathways, and promote the osteogenic differentiation of bone marrow mesenchymal stem cells. [11][12][13][14] There has been great progress in the development of silicate-based bioactive ceramics in the past decade. Many studies have conrmed that these ceramics can release Si ions to signicantly promote the proliferation and differentiation of bone cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other silicate-based bioactive materials, e.g., calcium silicate and bioactive glass, C2S can induce bone-like apatite mineralization in simulated body fluid [1,2]. Moreover, several studies have demonstrated that C2S could support the proliferation and differentiation of osteo-related cells, due to the release of Ca and Si [3,4,5,6,7]. However, it may be not enough to repair bone tissues with large defect size and poor osteogenic ability through C2S alone, as previous studies indicated that calcium silicate show limited effect on restoration of osteoporotic bone tissue [8].…”
Section: Introductionmentioning
confidence: 99%
“…C2S powder can be synthesized by different methods according to literature report, including solid state sintering [18] and the sol-gel method [2,7]. Solid state sintering with CaO and SiO 2 as raw materials tends to leave CaO residues, and its sintering temperature is higher than that of the so-gel method.…”
Section: Introductionmentioning
confidence: 99%